Effect of ICT-Based Learning Media on Student Learning Outcomes: A Scoping Review - Mochamad Kamil Budiarto; Asrowi; Gunarhadi; Sunardi; Abdul Rahman (Journal of Learning for Development)
The lack of innovative implementation of digital learning media presents obstacles to accessing course materials, leading to unequal learning opportunities among students and, subsequently, lower graduate competencies. This study aimed to review the research studies on the effects of implementing digital learning media in various formats and its contribution to students’ learning outcomes. This study employed a scoping review by analysing articles from reputable databases, including Scopus and Google Scholar, and using relevant keywords. The selected studies were examined through descriptive mapping and narrative synthesis to identify patterns in digital media usage and their impact on learning outcomes. The analysis recognised 29 pertinent investigations, revealing the prevailing pattern in research on digital learning media centres and on Mobile Applications and its influence on students’ educational achievements. Nevertheless, there is also a demand for other forms of digital learning media to be utilised in educational endeavours. Additionally, the findings of the research illustrate that the utilisation of digital learning media substantially improves students’ proficiency in both technical and interpersonal abilities. Consequently, this study serves as a valuable asset for educators, and urges them to adopt the incorporation of digital learning media.